Nexus Between Debt Financing and Market Value Moderated by Firm Size: Panel Data Evidence from India - Rajesh Desai
This study examines the effect of debt financing on market value of firm and evaluates the moderating effect of firm size on this relationship. Tobin$1 (Bs Q and market-to-book value ratio are used as proxy for market value whereas long-term as well as short-term debt ratios are considered to indicate debt financing. Using data of 164 capital goods sector companies for 10 years (from 2010 to 2019), panel least square (PLS) regression with fixed and random effects (RE) model has been applied for data analysis. Based on findings, the study reports significant negative impact of borrowings (both long-term and short-term) on market value of selected companies. Further, the outcome of study confirms that firm size moderates the relationship between debt financing and firm value. The magnitude and significance of the effect of debt are stronger for small firms as compared to medium and large firms. Present verdicts will assist managers in designing capital structure policies by considering its impact on market value according to firm-size.s